Implant quality assurance: detection of abscessed implants and their effect on feedlot performance of beef heifers - Spire, M.F.; Sargeant, J.M.; Blasi, Dale A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Infrared thermography (IRT) can be used successfully to differentiate abscessed implanted ears from nonimplanted ears 8 days postimplanting. Abscessed ears averaged 5.7EF warmer than nonimplanted ears when ambient temperature was 60 to 63EF. Average daily gain and feed efficiency were reduced 8.9% and 8.3%, respectively, over the 91-day feeding period for cattle with abscessed implants compared to cattle with normal implants. Dry matter intake was not affected by an abscessed implant and averaged nearly 18.0 lb/head/day for both treatment groups. Abscessed implants reduced economic return by $17.70 per head.
Keywords: Beef; Infrared thermography; Abscessed implants; Feedlot performance